2023
DOI: 10.1002/ardp.202200570
|View full text |Cite
|
Sign up to set email alerts
|

A new series of hydrazones as small‐molecule aldose reductase inhibitors

Abstract: In the search for small-molecule aldose reductase (AR) inhibitors, new tetrazolehydrazone hybrids (1-15) were designed. An efficient procedure was employed for the synthesis of compounds 1-15. All hydrazones were subjected to an in vitro assay to assess their AR inhibitory profiles. Compounds 1-15 caused AR inhibition with K i values ranging between 0.177 and 6.322 µM and IC 50 values ranging between 0.210 and 0.676 µM. 2-[(1-(4-Hydroxyphenyl)-1H-tetrazol-5-yl)thio]-N'-(4-fluorobenzylidene) acetohydrazide ( 4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Because of its polar nature, sorbitol finds it challenging to diffuse across cell membranes, which leads to osmotic imbalance [55] . This causes tissue damage from osmotic swelling and lens fiber cell rupture, which in turn leads to the development of cataracts [56,57] . In this study, the eye AR enzyme activity level of the studied groups are presented in Figure 2.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Because of its polar nature, sorbitol finds it challenging to diffuse across cell membranes, which leads to osmotic imbalance [55] . This causes tissue damage from osmotic swelling and lens fiber cell rupture, which in turn leads to the development of cataracts [56,57] . In this study, the eye AR enzyme activity level of the studied groups are presented in Figure 2.…”
Section: Resultsmentioning
confidence: 88%
“…[55] This causes tissue damage from osmotic swelling and lens fiber cell rupture, which in turn leads to the development of cataracts. [56,57] In this study, the eye AR enzyme activity level of the studied groups are presented in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the final reaction mixture, DMSO was present at a concentration of around 1 % [89] . To investigate the in vitro inhibitory mechanisms of these bis‐sulfides ( 5 a – i ) and bis‐sulfones ( 6 a – i ) against ALR2 [90–92] , the kinetic tests were conducted using Cerelli's method [93] at 340 nm, spectrophotometrically, and the DL‐glyceraldehyde (PubChem CID: 79014) was used as the substrate [94–97] . All the samples were measured three times.…”
Section: Methodsmentioning
confidence: 99%
“…[89] To investigate the in vitro inhibitory mechanisms of these bis-sulfides (5 a-i) and bis-sulfones (6 a-i) against ALR2 [90][91][92] , the kinetic tests were conducted using Cerelli's method [93] at 340 nm, spectrophotometrically, and the DL-glyceraldehyde (PubChem CID: 79014) was used as the substrate. [94][95][96][97] All the samples were measured three times. In accordance with our earlier research, IC 50 plots and Lineweaver-Burk curves [98] were made, and K I constants, their coefficient of determination (R 2 ), and inhibition types were determined based on the observed data.…”
Section: Biological Activity Studymentioning
confidence: 99%
“…The Small-Molecule Drug Discovery Suite 2022-3 for Mac (Schrödinger, LLC, NY, USA) was utilized to conduct in silico molecular docking study, as previously reported. [41,42] This suite includes the Maestro, Protein Preparation Wizard, [43,44] SiteMap, [45] LigPrep, [46] Receptor Grid Generation, [47] Ligand Docking, [48] and Prime MM-GBSA [49,50] tools. The Protein Data Bank (http://www.…”
Section: Docking Studymentioning
confidence: 99%